Räumliche Verteilungsaspekte von Schlüsseltechnologie-Industrien in den USA und in Kanada - Bathelt, Harald (ERDKUNDE, 1992)
Traditional location theory focuses on the analysis of location factors in explaining optimum location decisions of industrial firms. It implies that the specific locational advantages of regions cause a spatial differentiation of industrial firms and branches. This view is quite restrictive in that it does not allow location decisions which derive from corporate goals and strategies instead of locational characteristics. Especially in the case of key technology industries, it sems that traditional approaches are not capable of explaining the existing patterns of spatial concentration and sectoral specialization: key technology industries in the USA and in Canada have extremely concentrated within a small number of state/provinces and metropolitan areas. In addition, some industrial branches are characterized by different locational patterns, as well as a functional and organizational division of labour between regions. On a regional scale, key technology industries experience distinct specialization processes: agglomeration have developed with a high concentration of employment within a few dominant branches and large firms. A propper explanation of this spatial distribution can only be given by a dynamic-evolutionary industrial location theory in which agglomeration processes result from complex regional information-, technology-, labour market-, capital market- and input-output linkages. In such a concept, industries create new or reinforce existing locational advantages according to their needs. Regional growth processes are focused on the dominant industrial branches and result in distinct sectoral specialization patterns (e.g. local suppliers, labour markets, spin-offs and start-ups increasingly specialize in the same fields).